The Largest Reported Giant Ascending Aortic Aneurysm Presented with Superior Vena Cava Syndrome - Bicer,Murat (2020)
Abstract Giant ascending aortic aneurysm is a rare condition. In this paper, we present an uncommon case of giant ascending aortic aneurysm with a maximal diameter of 14 cm in a 77-year-old woman presenting with unusual symptoms. The patient underwent a successful surgery involving ascending aortic replacement, and was discharged without any complication. After discharge, she was followed regularly and no major problem was observed in her control visits. To the best of our knowledge, our case is the largest ascending aortic aneurysm reported to date in the existing literature.